Sedimentation rates by the 210Pb chronological method in Itanhaém river watershed, southeast Brazil - Cigagna, Cristiano [UNESP] (2021)
The historical variation of sedimentation rate was investigated in five cores collected from the Itanhaém watershed main rivers, the second largest coastal watershed of the São Paulo state, Brazil, using the lead-210 radioisotope as a geochronometer. The main characteristics of the rivers’ waters and sediments were determined in order to support the geochronological analysis results and associate sediments with possible source areas. In this context, the fluvial waters’ general classification indicated the facies sulfated or chlorinated sodium in the winter and summer seasons, except for the Branco river waters in summer, which were classified as calcium or magnesium bicarbonate. A longitudinal salinity gradient was found in the downstream river courses, under greater marine influence, with the ions Cl−, Na+, SO42+, Mg2+, Ca2+, and K+ being most common in the waters. Silica is the predominant constituent in the sediment cores and is inversely related to the organic matter (OM) presence. Inverse correlations were also found between silica and other constituents. The watershed sedimentation rates were determined in the range of 0.31 up to 3.97 g/cm2/year and 0.30 up to 3.40 cm/year, highlighting the core extracted from Branco river, which showed the highest sedimentation rate. The profiles corresponding to Preto and Aguapeú rivers presented discontinuities in the sedimentation rates. The discontinuities were dated and would probably be related to the anthropic activities, which intensified in the municipality of Itanhaém around the middle of the twentieth century.